L‐ornithine L‐aspartate in acute treatment of severe hepatic encephalopathy: A double‐blind randomized controlled trial. Issue 5 (21st December 2021) - Jain, Arpan; Sharma, Barjesh Chander; Mahajan, Bhawna; Srivastava, Siddharth; Kumar, Ajay; Sachdeva, Sanjeev; Sonika, Ujjwal; Dalal, Ashok
Abstract: Background and Aims: Data on the use of intravenous L‐ornithine L‐aspartate (LOLA) in the treatment of overt HE (OHE) is limited. We evaluated the role of intravenous LOLA in patients of cirrhosis with OHE grade III–IV. Approach and Results: In a double‐blind randomized placebo‐controlled trial, 140 patients were randomized to a combination of LOLA, lactulose, and rifaximin ( n  = 70) or placebo, lactulose, and rifaximin ( n  = 70). LOLA was given as continuous intravenous infusion at a dose of 30 g over 24 h for 5 days. Ammonia levels, TNF‐α, ILs, and endotoxins were measured on days 0 and 5. The primary outcome was the improvement in the grade of HE at day 5. Higher rates of improvement in grade of HE (92.5% vs. 66%, p  < 0.001), lower time to recovery (2.70 ± 0.46 vs. 3.00 ± 0.87 days, p  = 0.03), and lower 28‐day mortality (16.4% vs. 41.8%, p  = 0.001) were seen in the LOLA group as compared with placebo. Levels of inflammatory markers were reduced in both groups. Significantly higher reductions in levels of blood ammonia, IL‐6, and TNF‐α were seen in the LOLA group. Conclusions: Combination of LOLA with lactulose and rifaximin was more effective than only lactulose and rifaximin in improving grades of HE, recovery time from encephalopathy, with lower 28‐day mortality.